The teaching of programming: An experience in the training of Informatics teachers - Díaz Tejera, Keila Irena (2018)
The education of programming has between its main objectives, the development and the formation of skills on the part of the students, who make possible the resolution of problems of the school, professional or of the practical life taking into account the different resources that offer the languages of programming. In the training course of computer teachers, this process has some characteristics that distinguish it. The teachers to be must develop the skill and at the same time to appropriate of the necessary procedures to direct this process in the school. This article presents the main results obtained regarding this topic during the teaching learning process of several subjects of Programming in the training of Informatics teachers, with the systematization of living experiences, during nine years.